Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

By forming a carbon coating layer and an intermittent aluminum fluoride coating layer on the surface of lithium manganese oxide cathode material, the problem of manganese ion dissolution in manganese-based cathode materials at high temperatures is solved, thereby improving high-temperature cycle performance and rate performance.

CN120824356AActive Publication Date: 2025-10-21CHONGQING CHANGAN AUTOMOBILE CO LTD

Patent Information

Application Number
CN202511310410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-10-21
Estimated Expiration
2045-09-15

AI Technical Summary

Technical Problem

Existing manganese-based cathode materials suffer structural damage due to manganese ion dissolution at high temperatures, which reduces battery performance. Furthermore, traditional aluminum fluoride coating affects the material's rate performance and capacity.

Method used

By employing a combination of carbon coating and intermittent aluminum fluoride coating, a uniform and dense ultrathin aluminum fluoride coating is formed on the surface of lithium manganese oxide cathode material through atomic layer deposition, which inhibits the dissolution of manganese ions and improves the stability of the material.

Benefits of technology

It effectively inhibits manganese ion dissolution, improves high-temperature cycling performance, maintains excellent rate performance and capacity, and solves the problems of structural stability and electrochemical performance of manganese-based cathode materials at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120824356A_ABST
    Figure CN120824356A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a preparation method thereof, a positive electrode plate, a battery and an electric device. The positive electrode material comprises a positive electrode base material, a carbon coating layer and an aluminum fluoride coating layer, the positive electrode base material is coated with the carbon coating layer, and the carbon coating layer is coated with the aluminum fluoride coating layer; wherein the positive electrode base material is selected from lithium manganate; wherein the aluminum fluoride coating layer is a discontinuous coating layer. The positive electrode material has excellent high-temperature cycle performance and also has excellent rate capability and capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] The rapidly growing demand for lithium-ion batteries has placed significant pressure on the supply chains of metals such as nickel, cobalt, and lithium. To alleviate the pressure on nickel and cobalt supply, automakers and battery manufacturers are exploring manganese-based cathode materials as alternatives to nickel-rich cathode materials in appropriate applications. Manganese-based cathode materials have attracted widespread attention due to their low raw material costs and excellent low-temperature performance. Furthermore, manganese (Mn) is generally safer than nickel-rich cathode materials, and manganese (Mn) is one of the more abundant transition metals used in battery cell manufacturing. However, the dissolution of manganese ions due to various factors disrupts the structure of the cathode material. Furthermore, the dissolved manganese ions can deposit on the anode, degrading the solid electrolyte interphase (SEI) and leading to active material loss, consuming significant amounts of active lithium and causing significant battery capacity degradation. Mn ion dissolution is temperature- and voltage-dependent, significantly reducing the high-temperature performance of manganese-based cathode materials. Therefore, suppressing Mn ion dissolution in manganese-based cathode materials is crucial to improving their lifespan and promoting their application in batteries.

[0003] Common manganese-based cathode materials include lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based cathode materials, lithium iron manganese phosphate, nickel-cobalt-manganese NCM ternary materials, etc. Among these manganese-based cathode materials, the impact of manganese ion dissolution on the material stability is a more serious problem that must be solved in practical applications. As an example, spinel-type lithium manganese oxide with a spinel phase structure (where x = 0-0.2) can achieve a full capacity of 110 mAh / g and an average voltage of approximately 3.9 V, with an energy density comparable to that of lithium iron phosphate materials. Due to the three-dimensional Li diffusion channels within the spinel cathode material structure, spinel lithium manganese oxide cathode materials have high power density, making them suitable for many high-power applications. Their excellent processing properties, higher material compaction density, low cost, rich manganese storage capacity, and excellent rate performance have attracted attention in low-cost applications requiring moderate energy density and longevity, such as short-distance, low-cost electric vehicles and 3C consumer batteries.

[0004] At present, lithium manganese oxide material modification often adopts doping, coating and crystal face induction and other means to stabilize the crystal structure of the material and inhibit the Jahn-Teller effect and manganese ion dissolution. For example, Chinese patent application CN202510042662.3 realizes the synchronous and uniform doping of element M and element M' in the precursor stage through the co-precipitation method, and utilizes the synergistic effect of these elements in the subsequent sintering process to effectively stabilize the crystal structure of the lithium manganese oxide positive electrode material and realize the selective induced growth of the crystal face. This preferential orientation is conducive to inhibiting the dissolution of Mn and improving the stability of the lithium manganese oxide material. Chinese patent application CN202510025511.7 constructs a composite manganese-based positive electrode material with a core of lithium manganese oxide and an outer shell of a lithium-rich nickel-cobalt-manganese positive electrode material in the precursor preparation stage through the co-precipitation method, and prepares a manganese-based composite positive electrode material with high capacity, high safety, long cycle and high compaction. Chinese patent application CN202510302118.8 uses a sol-gel method to prepare a lithium triborate-coated lithium manganate cathode material. After annealing, the lattice structure stability of the lithium manganate cathode material is significantly improved, and manganese dissolution is inhibited. However, the existing technology still cannot achieve long-term high-temperature cycling performance of lithium manganate materials. Chinese patent application CN202010223608.6 uses Al, Zr, and F as ternary ion doping to modify lithium manganate, which can improve the order of lithium manganate to stabilize the spinel structure and inhibit lattice distortion. It also uses aluminum fluoride to coat the ternary ion-doped lithium manganate, which can effectively alleviate capacity decay, effectively prevent electrolyte corrosion, and reduce manganese ion dissolution. However, the non-conductive aluminum fluoride coating used in this invention patent application will affect the material's rate performance and capacity, and the coating layer formed by traditional coating methods is relatively uneven and the coating effect is also poor. While improving the stability of the base material, it will seriously affect the rate performance and capacity of the positive electrode material.

[0005] Therefore, it is necessary to provide a manganese-based positive electrode material that can effectively inhibit the dissolution of manganese ions, has excellent high-temperature cycle performance, and also has excellent rate performance and capacity. Summary of the Invention

[0006] In view of this, one of the objects of the present invention is to provide a positive electrode material, comprising a manganese-based positive electrode substrate, a carbon coating layer coated on the manganese-based positive electrode substrate, and an aluminum fluoride coating layer coated on the carbon coating layer, wherein the aluminum fluoride coating layer is a discontinuous coating layer. The carbon coating layer and the discontinuous aluminum fluoride coating layer work together to effectively suppress cyclic failure caused by manganese dissolution and subsequent deposition on the negative electrode side of the manganese-based positive electrode substrate due to electrolyte corrosion, thereby achieving excellent high-temperature cycling performance, as well as excellent rate performance and capacity.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode material, which includes a positive electrode base material, a carbon coating layer and an aluminum fluoride coating layer, the carbon coating layer is coated on the positive electrode base material, and the aluminum fluoride coating layer is coated on the carbon coating layer; wherein, the positive electrode base material is selected from lithium manganese oxide; wherein, the aluminum fluoride coating layer is an intermittent coating layer.

[0008] In some embodiments, the thickness of the aluminum fluoride coating layer is 1 nm to 30 nm.

[0009] In some embodiments, the positive electrode matrix material is selected from spinel lithium manganate , where x=0~0.2.

[0010] A second aspect of the present invention provides a method for preparing the positive electrode material according to the first aspect of the present invention, the method comprising the following steps: Step S1: mixing the positive electrode matrix material with a polymer solution to obtain a mixed solution, and drying the mixed solution to obtain a first intermediate product in which the polymer is uniformly attached to the surface of the positive electrode matrix material; The molar ratio is less than 1, The molar ratio is 0.01~0.5; Step S2: sintering the first intermediate product at a temperature of 150° C. to 400° C. in an inert gas atmosphere to obtain a second intermediate product; Step S3: placing the second intermediate product into an atomic layer deposition coating device, and sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device, so that aluminum fluoride is deposited on the second intermediate product to obtain a third intermediate product; Step S4: Tempering the third intermediate product at a temperature of 300° C. to 700° C. in an inert gas atmosphere to obtain the positive electrode material.

[0011] In some embodiments, in step S1, the polymer is selected from one or more of chitosan, polyvinyl alcohol, amino sugar, polyvinyl alcoholamine, and aminophenol-formaldehyde resin.

[0012] In some embodiments, in step S1, the drying is selected from one or more of spray drying, oven drying, and freeze drying.

[0013] In some embodiments, in step S2, the sintering time is 0.5 hours to 4 hours.

[0014] In some embodiments, in step S3, the operation of sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device is repeated multiple times until an aluminum fluoride coating layer with a thickness of 1 nm to 30 nm is obtained.

[0015] In some embodiments, in step S3, the aluminum source precursor is selected from one or more of trimethylaluminum, triethylaluminum, and aluminum triacetate.

[0016] In some embodiments, in step S3, the fluorine source precursor is selected from one or more of hydrogen fluoride, fluoromethane, and fluoroethane.

[0017] In some embodiments, in step S3, the cleaning agent is selected from one or more of nitrogen, helium, and argon.

[0018] In some embodiments, in step S3, the aluminum source precursor is introduced for a time period of 0.5 seconds to 30 seconds.

[0019] In some embodiments, in step S3, the fluorine source precursor is introduced for a time period of 0.5 seconds to 30 seconds.

[0020] In some embodiments, the cleaning agent is introduced for a time of 5 seconds to 150 seconds.

[0021] In some embodiments, in step S4, the tempering time is 1 hour to 6 hours.

[0022] The third aspect of the present invention provides a positive electrode material, which is prepared by the method of the second aspect of the present invention.

[0023] The fourth aspect of the present invention provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode material described in the first aspect of the present invention or the positive electrode material prepared by the method described in the second aspect of the present invention.

[0024] A fifth aspect of the present invention provides a battery, comprising the positive electrode sheet described in the fourth aspect of the present invention.

[0025] A sixth aspect of the present invention provides an electrical device, comprising the battery according to the fifth aspect of the present invention.

[0026] The beneficial effects of the present invention are as follows: (1) By depositing a carbon source on the positive electrode substrate, a certain amount of hydroxyl groups on the carbon source will react with aluminum fluoride and decompose, preventing aluminum fluoride from forming at the sites where hydroxyl groups are present, thereby obtaining a discontinuous aluminum fluoride coating. This discontinuous aluminum fluoride coating overcomes the problem of reduced material rate performance due to the poor conductivity of aluminum fluoride. On the other hand, carbon coating will form in areas without aluminum fluoride coating, which is beneficial to improving the material's conductivity and stabilizing the material surface, reducing side reactions between the electrolyte and the positive electrode material.

[0027] (2) During the sintering step, easily volatile groups such as amino groups in the polymer can be decomposed to provide sites and space for aluminum fluoride surface deposition. The aluminum fluoride coating area can then be precisely controlled by controlling the hydroxyl content. The aluminum fluoride coating area and coating thickness can be adjusted according to actual needs by selecting the hydroxyl content in the polymer to balance the material's rate and cycle performance.

[0028] (3) The aluminum fluoride coating formed by atomic layer deposition (ALD) is a uniform and dense ultra-thin coating that can effectively inhibit the side reactions at the interface between the electrolyte and the positive electrode material. At the same time, the ultra-thin coating formed by ALD has a smaller impact on the ion diffusion rate of the material than the traditional process, which is conducive to the performance of the material's rate performance. As a result, the positive electrode material has excellent rate performance.

[0029] (4) The manganese-based positive electrode material of the present invention can effectively inhibit the cycle failure caused by the dissolution of manganese ions due to electrolyte corrosion and their subsequent deposition on the negative electrode side, and has excellent high-temperature cycle performance, as well as excellent rate performance and capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the core-shell structure of the positive electrode materials prepared in Examples 1 to 4 of the present invention; Figure 2 This is a scanning electron microscope image (SEM) of the positive electrode material prepared in Comparative Example 1 of the present invention; Figure 3 This is a scanning electron microscope image (SEM) of the positive electrode material prepared in Example 1 of the present invention; Figure 4 The charge and discharge curves for the first two cycles of a button battery prepared using the positive electrode material prepared in Comparative Example 1 of the present invention are shown; Figure 5 The charge and discharge curves for the first two cycles of a button cell prepared using the positive electrode material prepared in Example 1 of the present invention are shown; Figure 6 A comparison chart of the charge capacity retention rate of 1.38Ah soft-pack batteries prepared using the positive electrode materials prepared in Comparative Example 1 and Example 1 of the present invention; Figure 7This is a comparison chart of the cycle retention rates of 1.38Ah soft-pack batteries prepared using the positive electrode materials prepared in Comparative Example 1, Comparative Example 3 and Example 1 of the present invention at 45°C.

[0031] Description of reference numerals: 1: positive electrode base material; 2: carbon coating layer; 3: aluminum fluoride coating layer. DETAILED DESCRIPTION

[0032] The following describes the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art will readily appreciate the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are intended only to illustrate the present invention and are not intended to limit the scope of protection of the present invention.

[0033] Manganese-based cathode materials have garnered widespread attention due to their low raw material costs and excellent low-temperature performance. Furthermore, they are generally safer than nickel-rich cathode materials, and manganese (Mn) is one of the more abundant transition metals used in battery cell manufacturing. However, the dissolution of manganese ions for various reasons disrupts the structure of the cathode material. Furthermore, the dissolved manganese ions deposit at the anode, degrading the solid electrolyte interphase (SEI) and leading to loss of active material, consuming significant amounts of active lithium and causing significant battery capacity degradation. Mn ion dissolution is temperature- and voltage-dependent, significantly reducing the high-temperature performance of manganese-based cathode materials.

[0034] In related technologies, aluminum fluoride is used to coat manganese-based positive electrode materials to alleviate capacity decay, prevent electrolyte corrosion, and reduce the dissolution of manganese ions. However, the aluminum fluoride coating used is non-conductive, which will affect the material's rate performance and capacity. Moreover, the coating layer formed by traditional coating methods is relatively uneven and the coating effect is also poor. While improving the stability of the positive electrode base material, it will seriously affect the rate performance and capacity of the positive electrode material.

[0035] Therefore, it is necessary to provide a manganese-based positive electrode material that can effectively inhibit the dissolution of manganese ions, has excellent high-temperature cycle performance, and also has excellent rate performance and capacity.

[0036] In view of this, the first aspect of the present invention provides a positive electrode material. The positive electrode material comprises a positive electrode base material, a carbon coating layer, and an aluminum fluoride coating layer, wherein the carbon coating layer is coated on the positive electrode base material, and the aluminum fluoride coating layer is coated on the carbon coating layer. The positive electrode base material is selected from lithium manganese oxide, and the aluminum fluoride coating layer is a discontinuous coating layer.

[0037] The positive electrode material of the present invention includes a manganese-based positive electrode matrix material, a carbon coating layer coated on the surface of the manganese-based positive electrode matrix material, and an aluminum fluoride coating layer coated on the carbon coating layer, wherein the aluminum fluoride coating layer is an intermittent coating layer. The aluminum fluoride coating layer can effectively inhibit the corrosion of the manganese-based positive electrode matrix material by the electrolyte and reduce the dissolution of manganese in the material. Since manganese dissolution will have a destructive effect on the negative electrode and the electrolyte, the aluminum fluoride coating greatly improves the stability of the positive electrode material, especially the high-temperature cycle performance of the material. On the other hand, the aluminum fluoride coating layer of the present invention is an intermittent discontinuous coating layer, which overcomes the reduction in material rate performance due to the poor electrical conductivity of aluminum fluoride. A carbon coating will be formed in the area without aluminum fluoride coating, which is beneficial to improving the electrical conductivity of the material and stabilizing the surface of the material, reducing the side reactions between the electrolyte and the positive electrode material. Therefore, under the combined action of the carbon coating layer and the discontinuous aluminum fluoride coating layer, the positive electrode material of the present invention can effectively inhibit the dissolution of manganese ions, has excellent high-temperature cycle performance, and also has excellent rate performance and capacity.

[0038] In some embodiments, the thickness of the aluminum fluoride coating layer is 1 nm to 30 nm. For example, the thickness of the aluminum fluoride coating layer can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, or a value within a range consisting of any two of these values. Alternatively, the thickness of the aluminum fluoride coating layer can be 1 nm to 10 nm, optionally 2 nm to 8 nm. The aluminum fluoride coating layer is beneficial for inhibiting the corrosion of the manganese-based positive electrode material by the electrolyte and reducing the dissolution of manganese in the material. Since manganese dissolution can have a destructive effect on the negative electrode and the electrolyte, the aluminum fluoride coating greatly improves the stability of the positive electrode material, especially the high-temperature cycle performance of the material. At the same time, the thickness of the aluminum fluoride coating layer in the present invention is relatively small. This ultra-thin aluminum fluoride coating has little effect on the ion diffusion rate of the positive electrode material, so while improving the stability of the positive electrode material, especially the high-temperature cycle performance of the material, it also has excellent rate performance.

[0039] In some embodiments, the weight percentage content of the carbon coating layer is 0.1% to 1.5% relative to the total weight of the positive electrode base material. For example, the weight percentage content of the carbon coating layer can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or a value between the ranges consisting of any two of these values ​​relative to the total weight of the positive electrode base material. The carbon coating layer has electrical conductivity. The carbon coating layer on the surface of the positive electrode base material forms a continuous conductive network, which helps to reduce the charge transfer impedance, thereby improving the electronic conductivity of the positive electrode material. On the other hand, the carbon coating layer can physically block the direct contact between the positive electrode base material and the electrolyte, further inhibiting the dissolution of manganese from the manganese-based positive electrode base material and the side reaction between the positive electrode base material and the electrolyte. Setting the weight percentage content of the carbon coating layer within the above range is conducive to the carbon coating layer playing the above role. If the carbon coating layer content exceeds its upper limit, it will have an adverse effect on the lithium ion transport of the positive electrode material. If the content of the carbon coating layer exceeds its lower limit, it has limited effect on improving the conductivity of the positive electrode material.

[0040] In some embodiments, the positive electrode matrix material is selected from spinel lithium manganate , where x=0~0.2.

[0041] In some embodiments, the positive electrode matrix material is selected from .

[0042] In some embodiments, the aluminum fluoride coating is formed by atomic layer deposition. Compared to traditional coating methods, the aluminum fluoride coating formed by atomic layer deposition is more uniform, dense, and ultra-thin. This ultra-thin aluminum fluoride coating can effectively inhibit interfacial side reactions between the electrolyte and the positive electrode material, while also having a smaller impact on the ion diffusion rate of the material, which is beneficial to the material's rate performance. As a result, the positive electrode material has excellent rate performance.

[0043] Another aspect of the present invention provides a method for preparing the positive electrode material of the first aspect of the present invention. The method comprises the following steps: Step S1: mixing the positive electrode matrix material with a polymer solution to obtain a mixed solution, and drying the mixed solution to obtain a first intermediate product in which the polymer is uniformly attached to the surface of the positive electrode matrix material; The molar ratio is less than 1, The molar ratio is 0.01~0.5; Step S2: sintering the first intermediate product at a temperature of 150° C. to 400° C. in an inert gas atmosphere to obtain a second intermediate product; Step S3: placing the second intermediate product into an atomic layer deposition coating device, and sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device, so that aluminum fluoride is deposited on the second intermediate product to obtain a third intermediate product; Step S4: Tempering the third intermediate product at a temperature of 300° C. to 700° C. in an inert gas atmosphere to obtain the positive electrode material.

[0044] In the method of the present invention, in the polymer used in step S1, the polymer The molar ratio is less than 1, The molar ratio is 0.01 to 0.5. For example, The molar ratio can be 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1 or a range between any two of these values. The molar ratio may be 0.1 to 0.3, and optionally 0.2 to 0.3. The molar ratio can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range between any two of these values. The molar ratio can be 0.01~0.3, optionally 0.05~0.2. A certain amount of hydroxyl groups are contained in the polymer, and these hydroxyl groups react with aluminum fluoride and decompose, so that aluminum fluoride deposition cannot be formed at the sites where hydroxyl groups are present, and aluminum fluoride deposition can be formed at the sites where hydroxyl groups are not present. As a result, a discontinuous aluminum fluoride coating can be formed on the surface of the substrate. Compared with the continuous aluminum fluoride coating, this discontinuous discontinuous aluminum fluoride coating overcomes the problem of reduced material rate performance caused by the poor electrical conductivity of aluminum fluoride. On the other hand, the area without aluminum fluoride coating will form a carbon coating, which is beneficial to improving the electrical conductivity of the material and stabilizing the surface of the material, reducing the side reactions between the electrolyte and the positive electrode material.

[0045] In the method of the present invention, in step S2, the first intermediate product is sintered at a temperature of 150°C to 400°C under an inert gas atmosphere to obtain a second intermediate product. For example, the sintering temperature can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 250°C, 300°C, 350°C, 400°C or a value between the ranges consisting of any two of them. Alternatively, the sintering temperature can be 150°C to 400°C, optionally 180°C. By sintering the first intermediate product at the above temperature, easily volatile groups such as amino groups in the polymer can be decomposed to provide sites and space for subsequent aluminum fluoride surface deposition, and then the coating area of ​​aluminum fluoride can be precisely controlled by controlling the content of hydroxyl groups. According to actual needs, the aluminum fluoride coating area and coating thickness can be adjusted by selecting the hydroxyl content in the polymer to balance the rate and cycle performance of the material.

[0046] In the method of the present invention, in step S3, a uniform and dense ultra-thin aluminum fluoride coating layer is formed by atomic layer deposition. The aluminum fluoride coating layer thus formed can effectively inhibit the interface side reaction between the electrolyte and the positive electrode material. At the same time, the ultra-thin coating layer deposited by ALD has less effect on the ion diffusion rate of the material than the traditional process, which is conducive to the performance of the material rate performance and is suitable for obtaining a positive electrode material with excellent rate performance.

[0047] In the method of the present invention, in step S4, the third intermediate product is tempered at a temperature of 300°C to 700°C under an inert gas atmosphere to obtain the positive electrode material. For example, the tempering temperature can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or a range consisting of any two of these values. Alternatively, the tempering temperature can be 400°C to 600°C. By performing tempering at the above temperature, the carbon source applied in step S1, i.e., the polymer, can be converted into carbon, thereby forming a carbon coating layer on the surface of the positive electrode substrate material. By performing tempering, the aluminum fluoride deposited in step S3 can also be converted into a more stable, more uniform, and more dense coating layer, thereby enhancing its ability to resist electrolyte corrosion.

[0048] In this article, The "molar ratio" refers to the molar ratio of nitrogen to carbon in the polymer. The nitrogen content in the polymer is related to nitrogen-containing groups such as amino groups. During the low-temperature sintering step, easily volatile groups such as amino groups in the polymer decompose, providing sites and space for aluminum fluoride surface deposition.

[0049] In this article, The "molar ratio" refers to the molar ratio of -OH groups and C elements in the polymer. The hydroxyl group is relatively more stable and will be retained during the low-temperature sintering step. During ALD aluminum fluoride coating, -OH will react with aluminum fluoride and decompose, making it impossible to form an aluminum fluoride coating layer at that location, thereby forming an intermittent and discontinuous aluminum fluoride coating layer.

[0050] Molar ratio and The molar ratio can be measured by conventional testing methods in the art, for example, elemental analysis, Dumas combustion method, chemical titration method, etc.

[0051] In some embodiments, in step S1, the polymer is selected from one or more of chitosan, polyvinyl alcohol, amino sugar, polyvinyl alcoholamine, and aminophenol-formaldehyde resin. Optionally, the polymer is selected from chitosan.

[0052] There are no particular restrictions on the solvent of the polymer solution, as long as it can dissolve the polymer. Optionally, the solvent has a low boiling point and is easily volatile, which facilitates the removal of the solvent during the subsequent drying process to obtain a first intermediate product in which the polymer is uniformly attached to the surface of the positive electrode substrate. In some embodiments, in step S1, the solvent of the polymer solution can be selected from one or more of water, ethanol, acetone, etc.

[0053] Regarding the concentration of the polymer solution, there is no particular restriction, as long as the polymer can be well dissolved at this concentration. Optionally, the concentration of the polymer solution can be 0.2wt%~20.0wt%. Exemplarily, the concentration of the polymer solution can be 0.2wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 10.0wt%, 15.0wt%, 20.0wt% or the value between the ranges consisting of any two of them. The concentration of the polymer solution is set within the above range, which is conducive to uniform adhesion of the polymer on the surface of the positive electrode base material, and subsequent drying operations.

[0054] There is no particular limitation on the drying method, as long as it does not change the structure and properties of the positive electrode matrix material and the polymer. In some embodiments, in step S1, the drying can be selected from one or more of spray drying, oven drying, and freeze drying.

[0055] In some embodiments, in step S1, the drying temperature may be 60°C to 150°C. For example, the drying temperature may be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or a range consisting of any two of these values. Alternatively, the drying temperature may be 80°C to 120°C, and optionally 120°C. Drying at the above temperature is beneficial for maintaining the structure and properties of the positive electrode matrix material and the polymer.

[0056] In some embodiments, in step S2, the sintering time can be 0.5 hours to 4 hours. For example, the sintering time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or a value between the ranges consisting of any two of them. Alternatively, the sintering time can be 1 hour. By sintering, easily volatile groups such as amino groups in the polymer can be removed, thereby providing sites and space for subsequent surface deposition of aluminum fluoride. During the sintering process, these groups undergo decomposition reactions. However, during the sintering process, due to the choice of reaction temperature and time, hydroxyl groups and carbon skeletons will not be affected. During the sintering process, hydroxyl groups are retained, thereby suppressing the deposition of aluminum fluoride at sites with hydroxyl groups in the subsequent ALD deposition process. Aluminum fluoride can be deposited at sites without hydroxyl groups, but on the contrary, aluminum fluoride cannot be deposited at sites with hydroxyl groups. Thus, an intermittent discontinuous aluminum fluoride coating can be formed.

[0057] In some embodiments, in step S3, the operation of sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device is repeated multiple times until an aluminum fluoride coating layer with a thickness of 1 nm to 30 nm is obtained. In the present invention, "sequentially passing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the ALD coating device" can be referred to as a cycle. Each cycle can form a very thin aluminum fluoride layer on the surface of the substrate. By performing multiple cycles, the aluminum fluoride layer can be evenly coated on the entire surface of the substrate to avoid local over-thickness or over-thinness. A deposition layer of a certain thickness is formed in each cycle, and by performing multiple cycles, the desired thickness can be gradually accumulated. In this way, a uniform ultra-thin aluminum fluoride coating layer can be obtained.

[0058] In some embodiments, in step S3, the aluminum source precursor is selected from one or more of trimethylaluminum, triethylaluminum, and aluminum triacetate. Alternatively, the aluminum source precursor is selected from trimethylaluminum. During the atomic layer deposition process, the aluminum source precursor is used to provide aluminum to react with the fluorine source precursor to form the target compound aluminum fluoride, thereby forming the desired aluminum fluoride coating on the material surface.

[0059] In some embodiments, in step S3, the fluorine source precursor is selected from hydrogen fluoride, fluoromethane ( ), fluoroethane ( ) or more thereof. Optionally, the fluorine source precursor is selected from fluoroethane. During the atomic layer deposition process, the fluorine source precursor is used to provide fluorine to react with the aluminum source precursor to form the target compound aluminum fluoride, thereby forming the desired aluminum fluoride coating on the material surface.

[0060] In some embodiments, in step S3, the cleaning agent is selected from one or more of nitrogen, helium, and argon. The cleaning agent is used to purge unreacted precursor materials remaining in the atomic layer deposition (ALD) coating equipment and reaction byproducts generated during the reaction process out of the reaction chamber, thereby reducing the interference of these substances with the subsequent deposition process. The selected cleaning agents, such as nitrogen and helium, are chemically inert and can effectively remove reaction byproducts and unreacted precursors without negatively affecting the deposition process, thereby facilitating the formation of a uniformly deposited, high-quality aluminum fluoride coating layer.

[0061] In some embodiments, in steps S2 and S4, the inert gas may be selected from one or more of nitrogen, helium, and argon, wherein the purity of the gas is above 98% and the oxygen content is below 0.01%.

[0062] In some embodiments, in step S3, the introduction time of the aluminum source precursor can be 0.5 seconds to 30 seconds. For example, the introduction time of the aluminum source precursor can be 0.5 seconds, 1 second, 2 seconds, 4 seconds, 6 seconds, 8 seconds, 10 seconds, 12 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds or a value between the ranges consisting of any two of these values. Optionally, the introduction time of the aluminum source precursor can be 1 second. During the atomic layer deposition process, the aluminum element can be introduced into the reaction system by introducing the aluminum source precursor. The aluminum source precursor chemically adsorbs on the surface of the substrate to form a uniform aluminum atomic layer, which reacts with the introduced fluorine source precursor to form a uniform and ultra-thin aluminum fluoride deposition layer. By setting the introduction time of the aluminum source precursor within the above range, it is beneficial to deposit a uniform and ultra-thin aluminum fluoride deposition layer.

[0063] In some embodiments, in step S3, the passage time of the fluorine source precursor can be 0.5 seconds to 30 seconds. For example, the passage time of the fluorine source precursor can be 0.5 seconds, 1 second, 2 seconds, 4 seconds, 6 seconds, 8 seconds, 10 seconds, 12 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds or a value between the ranges consisting of any two of them. Alternatively, the passage time of the fluorine source precursor can be 1 second. During the atomic layer deposition process, fluorine element can be introduced into the reaction system by passing through a fluorine source precursor. The fluorine source precursor chemically adsorbs on the surface of the substrate to form a uniform layer of fluorine atoms, which reacts with the introduced aluminum source precursor to form a uniform and ultra-thin aluminum fluoride deposition layer. By setting the passage time of the fluorine source precursor within the above range, it is beneficial to deposit a uniform and ultra-thin aluminum fluoride deposition layer.

[0064] In some embodiments, in step S3, the time for passing the cleaning agent can be 5 seconds to 150 seconds. For example, the time for passing the cleaning agent can be 5 seconds, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, 80 seconds, 100 seconds, 120 seconds, 150 seconds or a value between the ranges consisting of any two of them. Alternatively, the time for passing the cleaning agent can be 30 seconds. During atomic layer deposition, by passing the cleaning agent, the unreacted precursor raw materials remaining in the atomic layer deposition ALD coating equipment and the reaction byproducts generated during the reaction can be purged out of the reaction chamber, reducing the interference of these substances with the subsequent deposition process. This is conducive to forming a high-quality aluminum fluoride coating layer with uniform deposition. By setting the time for passing the cleaning agent within the above range, it is conducive to achieving the above purpose.

[0065] In some embodiments, in step S4, the tempering time can be 1 hour to 6 hours. For example, the tempering time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or a value between the ranges consisting of any two of these values. Alternatively, the tempering time can be 3 hours. By performing tempering, the carbon source applied in step S1, i.e., the polymer, can be converted into carbon, thereby forming a carbon coating layer on the surface of the positive electrode substrate material. By performing tempering, the aluminum fluoride deposited in step S3 can also be converted into a more stable, more uniform, and denser coating layer, thereby enhancing its ability to resist electrolyte corrosion. By setting the tempering time within the above range, it is beneficial to achieve the purpose of the above tempering.

[0066] A third aspect of the present invention provides a positive electrode material, which is prepared by the method of the second aspect of the present invention.

[0067] A fourth aspect of the present invention provides a positive electrode plate. The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode material described in the first aspect of the present invention, or a positive electrode material prepared by the method described in the second aspect of the present invention.

[0068] The positive electrode current collector has two surfaces facing each other in its thickness direction. The positive electrode active material layer may be provided on either or both of the two facing surfaces of the positive electrode current collector.

[0069] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, or silver alloy on a polymer substrate. For example, the polymer material may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and the like.

[0070] A fifth aspect of the present invention provides a battery comprising the positive electrode sheet described in the fourth aspect of the present invention.

[0071] The sixth aspect of the present invention provides an electrical device comprising the battery according to the fifth aspect of the present invention.

[0072] The embodiments of the present invention are described in detail below with reference to the examples and drawings. It should be understood that the following examples are only for illustrative purposes only and should not be construed as limiting the present invention.

[0073] Example 1 (1) 100g of chemical formula The lithium manganate positive electrode matrix material was fully mixed with 25 mL of chitosan aqueous solution (the concentration of the chitosan aqueous solution was 2 wt%) to obtain a mixed solution, wherein the chitosan The molar ratio is about 0.2, The molar ratio is about 0.05, and the mixed solution is dried by spray drying at a drying temperature of 120° C. to obtain a first intermediate product in which the polymer is uniformly attached to the surface of the positive electrode base material.

[0074] (2) The obtained first intermediate product was sintered in a box furnace at 180° C. for 1 hour in a nitrogen atmosphere to decompose the amino groups of chitosan and obtain a second intermediate product.

[0075] (3) The second intermediate product obtained in step (2) is placed in an atomic layer deposition (ALD) coating device, trimethylaluminum is first introduced and reacted for 1 second to complete aluminum deposition, nitrogen is then introduced for 20 seconds for cleaning, fluoroethane is then introduced for 1 second to carry out fluorine deposition, and nitrogen is then introduced for 30 seconds for cleaning, and the above steps are repeated until the deposition thickness of the aluminum fluoride coating reaches 2 nm to obtain a third intermediate product, which is then taken out.

[0076] (4) The third intermediate product, i.e., the ALD-coated sample, was tempered in a box furnace at 600°C for 3 hours under a nitrogen atmosphere to obtain a lithium manganate positive electrode substrate material discontinuously coated with aluminum fluoride.

[0077] Example 2 The positive electrode material was prepared in the same manner as in Example 1, except that the chitosan used in step (1) of Example 1 was replaced by The molar ratio is about 0.2, The molar ratio of chitosan is about 0.2.

[0078] Example 3 The positive electrode material was prepared in the same manner as in Example 1, except that the chitosan used in step (1) of Example 1 was replaced by The molar ratio is about 0.3, The molar ratio of chitosan is about 0.05.

[0079] Example 4 The positive electrode material was prepared in the same manner as in Example 1, except that the number of repetitions of the steps of introducing trimethylaluminum, then introducing nitrogen, then introducing fluoroethane, and then introducing nitrogen in step (3) of Example 1 was changed until the deposition thickness of the aluminum fluoride coating reached 4 nm.

[0080] The core-shell structure schematic diagram of the positive electrode materials prepared in Examples 1 to 4 is shown in FIG. Figure 1 In. From Figure 1 As can be seen in the figure, a continuous carbon coating layer 2 is coated on the surface of the positive electrode base material 1, and an intermittent, discontinuous aluminum fluoride coating layer 3 is coated on the carbon coating layer 2. A carbon coating is formed at the discontinuities of the aluminum fluoride coating layer. The combined action of the carbon coating layer and the intermittent aluminum fluoride coating layer effectively suppresses the cyclic failure caused by manganese dissolution caused by electrolyte corrosion in the positive electrode base material 1 and subsequent deposition on the negative electrode side, resulting in excellent high-temperature cycling performance of the positive electrode material while taking into account the rate performance and capacity of the positive electrode material.

[0081] Comparative Example 1 The positive electrode material was prepared in the same manner as in Example 1, except that the sintering temperature in step (2) of Example 1 was replaced with 600° C. and the sintering time was replaced with 3 hours. Therefore, in the sintering step of step (2), the carbon source applied in step (1) had been sintered and converted into carbon.

[0082] Comparative Example 2 (1) 100g of chemical formula The lithium manganese oxide positive electrode substrate material is placed in the atomic layer deposition ALD coating equipment, trimethylaluminum is first introduced and reacted for 1 second to complete aluminum deposition, then nitrogen is introduced for 20 seconds for cleaning, and then fluoroethane is introduced for 1 second to carry out fluorine deposition, and then nitrogen is introduced for 30 seconds for cleaning, and the above steps are repeated until the deposition thickness of the aluminum fluoride coating layer reaches 2nm to obtain an intermediate product, and then the intermediate product is taken out.

[0083] (2) The aluminum fluoride-coated lithium manganate positive electrode substrate material was tempered in a box furnace at a temperature of 600° C. for 3 hours under a nitrogen atmosphere to obtain a lithium manganate positive electrode substrate material continuously coated with aluminum fluoride.

[0084] Comparative Example 3 Directly take the chemical formula The lithium manganese oxide positive electrode matrix material is used as the positive electrode material.

[0085] The positive electrode matrix materials and chitosan used in Examples 1 to 4 Molar ratio, The molar ratio, thickness of the aluminum fluoride coating layer, tempering temperature, and tempering time are shown in Table 1 below.

[0086] Table 1

[0087] The positive electrode matrix materials and chitosan used in Example 1 and Comparative Examples 1 to 3 Molar ratio, The molar ratios and some of the preparation conditions are shown in Table 2 below.

[0088] Table 2

[0089] Figure 2 ] shows a scanning electron microscope image (SEM) of the positive electrode material prepared in Comparative Example 1. Figure 3 The SEM image of the cathode material prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that the surface of the positive electrode material obtained by continuous ALD coating is smooth and uniform, and the shape is regular. Figure 3It can be seen that the surface of the positive electrode material prepared in Example 1 of the present invention is rougher than that in Comparative Example 1, which is caused by discontinuous aluminum fluoride coating.

[0090] Buckle batteries were prepared using the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 3. The battery case used was CR2025 and the negative electrode was a lithium sheet. The discharge capacity at 25°C and 0.1C rate and the capacity retention rate after 60 cycles at 50°C were tested. The constant current charge and discharge test was carried out within the voltage window of 3.0-4.3V. The test results of the buckle batteries are shown in Table 3 and Table 4. Figures 4 and 5 middle.

[0091] Table 3

[0092] As can be seen from Table 3, the positive electrode material obtained by the method of the present invention can achieve a balance between capacity and high-temperature cycle stability, while in Comparative Examples 1 to 3, the three materials cannot achieve both high capacity and excellent cycle stability. Specifically, the positive electrode material without any coating (Comparative Example 3) showed a capacity of 125.41 mAh g -1 The high-temperature cycle performance of the positive electrode material fully coated with aluminum fluoride (Comparative Examples 1 and 2) was better, but its capacity was reduced to 110.52 mAh g -1 and 108.16mAh g -1 , the capacity of the positive electrode material in Example 1 of the present invention is significantly lower than that of the uncoated material (Comparative Example 3). -1 , the high-temperature cycle performance is comparable to that of the fully coated positive electrode material (Comparative Examples 1 and 2). In Example 2, the hydroxyl content in chitosan is increased compared to that in Example 1, and the hydroxyl content is related to the aluminum fluoride coating area. When the hydroxyl content increases, the aluminum fluoride coating area decreases. When the aluminum fluoride coating area decreases, the capacity of the positive electrode material is slightly improved compared to that in Example 1, and the cycle performance is slightly reduced. In Example 3, although the amino content in chitosan is increased compared to that in Example 1, the capacity and high-temperature cycle performance of the positive electrode material are comparable to those of the positive electrode material in Example 1. In Example 4, the thickness of the aluminum fluoride coating layer is increased, the high-temperature cycle performance is improved, and the capacity is slightly reduced. In summary, the positive electrode materials with discontinuous aluminum fluoride coating layers in Examples 1 to 4 have better capacity than the positive electrode materials of Comparative Examples 1 and 2 that are completely coated with aluminum fluoride, and at the same time, the high-temperature cycle performance is comparable to that of Comparative Examples 1 and 2.

[0093] Figure 4 The first two charge and discharge curves of the button cell prepared using the positive electrode material prepared in Comparative Example 1 of the present invention are shown. Figure 4It can be seen that the first efficiency and capacity of the positive electrode material are low.

[0094] Figure 5 The first two charge and discharge curves of the button cell prepared using the positive electrode material prepared in Example 1 of the present invention are shown. Figure 5 It can be seen that the initial efficiency of this material is significantly improved compared with comparative example 1, and the capacity is higher.

[0095] A 1.38Ah soft pack battery was prepared using the positive electrode materials of Example 1, Comparative Example 1, and Comparative Example 3, wherein the negative electrode material was graphite and the separator was a PE ceramic separator. At 25°C, the material double charge capacity retention rate was tested at 1C, 2C, 3C, and 4C; and the high temperature cycle capacity retention rate was tested at 45°C. The test voltage window was 3.0-4.2 V. The test results of the soft pack battery are shown in Figure 6 and Figure 7 middle.

[0096] from Figure 6 It can be seen that the charge capacity retention rate of the positive electrode material with the discontinuous aluminum fluoride coating layer in Example 1 of the present invention is better than that of the positive electrode material with the continuous aluminum fluoride coating layer in Comparative Example 1. Figure 7 It can be seen that compared with the positive electrode material without aluminum fluoride coating in comparative example 3, the high temperature cycle stability of the positive electrode material with discontinuous aluminum fluoride coating in Example 1 of the present invention is significantly improved, and its high temperature cycle stability is comparable to that of the positive electrode material with continuous aluminum fluoride coating in comparative example 1. Figure 6 and Figure 7 From the above, the positive electrode material of the discontinuous aluminum fluoride coating layer of the present invention has excellent rate performance while improving high-temperature cycle stability.

[0097] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or modification made by those skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that The positive electrode material includes a positive electrode base material, a carbon coating layer and an aluminum fluoride coating layer, wherein the carbon coating layer is coated on the positive electrode base material, and the aluminum fluoride coating layer is coated on the carbon coating layer; wherein the positive electrode base material is selected from lithium manganese oxide; wherein the aluminum fluoride coating layer is an intermittent coating layer.

2. The positive electrode material according to claim 1, wherein The thickness of the aluminum fluoride coating layer is 1 nm to 30 nm.

3. The positive electrode material according to claim 1 or 2, wherein The positive electrode matrix material is selected from spinel lithium manganate , where x=0~0.

2.

4. A method for preparing the positive electrode material according to claim 1, characterized in that: The method comprises the following steps: Step S1: mixing the positive electrode matrix material with a polymer solution to obtain a mixed solution, and drying the mixed solution to obtain a first intermediate product in which the polymer is uniformly attached to the surface of the positive electrode matrix material; The molar ratio is less than 1, The molar ratio is 0.01~0.5; Step S2: sintering the first intermediate product at a temperature of 150° C. to 400° C. in an inert gas atmosphere to obtain a second intermediate product; Step S3: placing the second intermediate product into an atomic layer deposition coating device, and sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device, so that aluminum fluoride is deposited on the second intermediate product to obtain a third intermediate product; Step S4: Tempering the third intermediate product at a temperature of 300° C. to 700° C. in an inert gas atmosphere to obtain the positive electrode material.

5. The method according to claim 4, wherein In step S1, the polymer is selected from one or more of chitosan, polyvinyl alcohol, amino sugar, polyvinyl alcoholamine, and aminophenol-formaldehyde resin.

6. The method according to claim 4 or 5, wherein: In step S1, the drying is selected from one or more of spray drying, oven drying, and freeze drying.

7. The method according to claim 4 or 5, wherein: In step S2, the sintering time is 0.5 hours to 4 hours.

8. The method according to claim 4 or 5, wherein: In step S3, the operation of sequentially introducing an aluminum source precursor, a cleaning agent, a fluorine source precursor, and a cleaning agent into the device is repeated multiple times until an aluminum fluoride coating layer with a thickness of 1 nm to 30 nm is obtained.

9. The method according to claim 4 or 5, wherein: In step S3, the aluminum source precursor is selected from one or more of trimethylaluminum, triethylaluminum, and aluminum triacetate.

10. The method according to claim 4 or 5, wherein: In step S3, the fluorine source precursor is selected from one or more of hydrogen fluoride, fluoromethane, and fluoroethane.

11. The method according to claim 4 or 5, wherein: In step S3, the cleaning agent is selected from one or more of nitrogen, helium, and argon.

12. The method according to claim 4 or 5, wherein: In step S3, the aluminum source precursor is introduced for a time period of 0.5 seconds to 30 seconds; and / or, The fluorine source precursor is introduced for a time period of 0.5 seconds to 30 seconds; and / or The cleaning agent is introduced for a time of 5 seconds to 150 seconds.

13. The method according to claim 4 or 5, wherein: In step S4, the tempering time is 1 hour to 6 hours.

14. A positive electrode plate, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the method according to any one of claims 4 to 13.

15. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 14.

16. An electrical device, characterized in that: The electrical device comprises the battery according to claim 15.

Citation Information

Patent Citations

  • A ternary doped lithium manganese oxide cathode material coated with aluminum trifluoride and its preparation method

    CN111403710B

  • Lithium Manganate Cathode Material Coated with Lithium Triborate and Preparation Method Thereof

    CN119812292B

  • Lithium manganate precursor with crystal face induction effect, preparation method of lithium manganate precursor, positive electrode material and lithium battery

    CN119822411A

  • Manganese-based composite positive electrode material and preparation method and application thereof

    CN119833606A

  • Embedded nano-compound coated modified cathode material for lithium ion battery and preparation method of cathode material

    CN104577095A

Cited By

  • Manganese-based lithium battery, preparation method thereof and power utilization device comprising manganese-based lithium battery

    CN120545363A

  • Manganese-based lithium battery and preparation method thereof, and electric device comprising the manganese-based lithium battery

    CN120545363B